Impact of 3-week citrulline supplementation on postprandial protein metabolism in malnourished older patients: The Ciproage randomized controlled trial. Issue 2 (April 2019) - Bouillanne, Olivier; Melchior, Jean-Claude; Faure, Cécile; Paul, Muriel; Canouï-Poitrine, Florence; Boirie, Yves; Chevenne, Didier; Forasassi, Christine; Guery, Ester; Herbaud, Stéphane; Le Corvoisier, Philippe; Neveux, Nathalie; et al.
Summary: Background: Citrulline (CIT), is not extracted by the splanchnic area, can stimulate muscle protein synthesis and could potentially find clinical applications in conditions involving low amino acid (AA) intake, such as in malnourished older subjects. Objective: Our purpose was to research the effects of CIT supplementation on protein metabolism in particular on non-oxidative leucine disposal (NOLD, primary endpoint), and splanchnic extraction of amino acids in malnourished older patients. Design: This prospective randomized multicenter study determined whole-body and liver protein synthesis, splanchnic protein metabolism and appendicular skeletal muscle mass (ASMM) in 24 malnourished older patients [80–92 years; 18 women and 6 men] in inpatient rehabilitation units. All received an oral dose of 10 g of CIT or an equimolar mixture of six non-essential amino acids (NEAAs), as isonitrogenous placebo, for 3 weeks. Results: NOLD and albumin fractional synthesis rates were not different between the NEAA and CIT groups. Splanchnic extraction of dietary amino acid tended to decrease ( p  = 0.09) in the CIT group (45.2%) compared with the NEAA group (60.3%). Total differences in AA and NEAA area under the curves between fed-state and postabsorptive-state were significantly higher in the CIT than in the NEAA group. There were no significant differences for body mass index, fat mass (FM), lean mass (LM) or ASMM in the whole population except for a tendential decrease in FM for the citrulline group ( p  = 0.089). Compared with Day 1, lean mass and ASMM significantly increased (respectively p  = 0.016 and p  = 0.018) at Day 20 in CIT-treated women (mean respective increase of 1.7 kg and 1.1 kg), and fat mass significantly decreased ( p  = 0.001) at Day 20 in CIT-group women (mean decrease of 1.3 kg). Conclusions: Our results demonstrate that CIT supplementation has no effect on whole-body protein synthesis or liver protein synthesis in malnourished older subjects. However, CIT supplementation was associated with a higher systemic AA availability. In the subgroup of women, CIT supplementation increased LM and ASMM, and decreased FM.